A novel graph theory based two-stage minimum cost routing mechanism in energy internet. (November 2022) - Ji, Xiaotong; Liu, Dan; Xiao, Fan; Du, Yunfei; Xiong, Ping; Jiang, Lang
Highlights: Day-ahead and intraday two-stage energy routing mechanisms are proposed. An MCR algorithm with the weight of the cost is proposed to support the mechanism. An equal-cost incremental principle is proposed for special operating conditions. Abstract: Energy internet is a multi-energy system with "source-network-load-storage" coordinated and optimized operation, and the research on the routing mechanism of its core equipment called electric energy router (EER) is a significant aspect of the energy optimization in the energy internet. In this paper, the existing EERs routing mechanisms are improved in terms of optimization objectives, congestion management, and heavy load power supply. Firstly, the structure and function of the EER are described from the perspective of the network, and the topology of the energy internet is designed based on graph theory. Secondly, in combination with the concept of virtual circuit transmission, open shortest path first routing algorithm, policy-based routing, and routing policy in information internet, a two-stage routing mechanism of day-ahead peer-to-peer transaction and intraday power balance is proposed. Furthermore, a minimum cost routing selection algorithm with the cost weight coefficients is also proposed to support the studied mechanism. Besides, an equal-cost incremental principle is proposed to optimize transmission congestion management and heavy load power supply, which can realize the lowest cost transmission through the least path. Finally, the routing mechanism is verified by case analyses which prove the relevance of the proposed method.